First report on black spot of rose (Rosa indica L.) caused by Colletotrichum siamense from India - Moitreyee Das; Phanindra P V; Parul; Priyanshu Gupta; Shyam Saran Vaish (Physiological and Molecular Plant Pathology, 2026)

Photocatalytic degradation of methylene red dye using biosynthesized silica coated semiconductor photocatalyst - M A Ashwini; Yashneeti Mehta; Anita Gupta; Kumar Rakesh Ranjan; Maumita Das Mukherjee; Parul Khurana; Sheenam Thatai (Next Research, 2026)

Synthesis of Diosgenin by Pseudomonas aeruginosa D3, an Endophyte of Dioscorea bulbifera - Krishna Nanda Dhal; Pramod Kumar Sahu; Amrita Gupta; Adarsh Kumar; Zaryab Shafi; Parul Johri; Sushma Mishra; Alok Kumar Srivastava (Current Microbiology, 2026)

Boosting β-carotene in rice and wheat grains through seed-specific expression of a modified wheat or gene - Parul Sirohi; Ritika Vishnoi; Suchi Baliyan; Bidya Bhushan Gupta; Pratibha Demiwal; Hugo Germain; Debabrata Sircar; Harsh Chauhan (Transgenic Research, 2026)

Regional distribution and seasonal histomorphology of cell types of pars distalis adenohypophysis of Gaddi goats: A comparative study between the year 2001 and the present in the context of climate change - Arjun Kumar Rao; Virender Pathak; Rajesh Rajput; Divya Gupta; Parul Shukla (Tropical Animal Health and Production, 2026)

Geospatial monitoring of peri-urban zones in Chandigarh through multi-year landsat imagery - Jyoti Saini; Umesh Kumar; Anil Kumar Gupta; Parul Mishra; Ratchagaraja Dhairiyasamy; Deekshant Varshney; Subhav Singh (Urban Ecosystems, 2025)

YTHDC1 orchestrates oncogenic splicing via the CLK1-SRSF1 splicing machinery to regulate castration-resistant prostate cancer progression - Parth Gupta; Devesh Srivastava; Vinayak Nayak; B Vishal Rao; K. Suseela; Rakesh Sharma; Senthil J. Rajappa; T. Subramanyeshwar Rao; Parul Mishra; Ashish Misra (Molecular and Cellular Biochemistry, 2025)

Retraction Note: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2025)

Graphical analysis of multi-environmental trials for rose scented geranium (Pelargonium graveleons L'H'er.L'Herit ex Ait) essential oil yield using GGE biplot analysis - Ashish Kumar; Nilesh Sharma; Anil Kumar Gupta; Anju Yadav; Parul Sharma; C.S. Chanotiya; R.K. Lal (Biochemical Systematics and Ecology, 2025)

ALR inhibits HBV replication and autophagosome formation by ameliorating HBV-induced ROS production in hepatic cells - Amit Kumar Mishra; Md. Musa Hossain; Teja Naveen Sata; Kishor Pant; Ajay K. Yadav; Amrendra Kumar Sah; Parul Gupta; Md Ismail; Baibaswata Nayak; Shalimar; Senthil Kumar Venugopal (Virus Genes, 2025)

Use of discarded corneo-scleral rims to create cornea-like tissue - Maryada Sharma; Subhpreet Kaur; Nimisha A. Mavlankar; Alokananda Chanda; Parul Chawla Gupta; Uma Nahar Saikia; Jagat Ram; Asish Pal; Sanjay Mandal; Purnananda Guptasarma; Manni Luthra-Guptasarma (Molecular Biology Reports, 2024)

Isolation and Characterization of Extended-Spectrum β-Lactamase Producing Escherichia coli from Pig Farms and Slaughterhouse - Jagana Niharika; Rajib Deb; Ranjeet Parihar; Priyanka Kumari Thakur; Pranav Anjaria; Gyanendra Singh Sengar; Parul Chaudhary; Seema Rani Pegu; Nitin Attupurum; Naveena Antony; Swaraj Rajkhowa; Vivek Kumar Gupta (Indian Journal of Microbiology, 2024)

Assessment of higher demand of household energy consumption in different households in India: an inter-comparative study and solar savings valuation - Abhishek Saxena; Atul A. Sagade; Erdem Cuce; Desh Bandhu Singh; Avnish Kumar; Parul Gupta (Environmental Science and Pollution Research, 2024)

A review on hospital wastewater treatment technologies: Current management practices and future prospects - Geeta Bhandari; Parul Chaudhary; Saurabh Gangola; Sanjay Gupta; Ashulekha Gupta; Mohd Rafatullah; Shaohua Chen (Journal of Water Process Engineering, 2023)

Correction to: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2023)

Characterization of piggery farm waste-borne bacterial transposable elements associated with antimicrobial resistance phenotypes - Priyanka Kumari Thakur; Rajib Deb; Seema Rani Pegu; Ranjeet Parihar; Jagana Niharika; Pranab Jyoti Das; Gyanendra Singh Sengar; Joyshikh Sonowal; Parul Chaudhary; Arutkumaran Selvaradjou; Atul Raj; Vivek Kumar Gupta (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Nanoencapsulation of Docetaxel Induces Concurrent Apoptosis and Necroptosis in Human Oral Cancer Cells (SCC-9) via TNF-α/RIP1/RIP3 Pathway - Parul Gupta; Arpita Singh; Ajay Kumar Verma; Surya Kant; Anuj Kumar Pandey; Anupam Mishra; Puneet Khare; Ved Prakash (Indian Journal of Clinical Biochemistry, 2023)

Developing resistance against soil-borne Fusarium pathogen causing tomato wilt through in vitro cell line selection - Ishani Shaunak; Rajnish Sharma; Parul Sharma; Meenu Gupta; Ramesh Kumar Bhardwaj (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Glyphosate-resistant Brassica juncea (oilseed mustard) transgenics for possible control of root parasite Orobanche aegyptiaca and conservation agriculture - Parul Agarwal; Arundhati Mukhopadhyay; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2022)

RETRACTED ARTICLE: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2022)

Interpreting HbA1c in Presence of Deficiency Anemias - Seema Bhargava; Khageshwar Mahato; Anjali Manocha; Mamta Kankra; Parul Singla; Anisha Sharma; Ashok Ahirwar; Vinod Gupta; Salamma Jose (Indian Journal of Clinical Biochemistry, 2021)

Gut microbiome contributes to impairment of immunity in pulmonary tuberculosis patients by alteration of butyrate and propionate producers - Abhijit Maji; Richa Misra; Darshan B. Dhakan; Vipin Gupta; Nitish K. Mahato; Rituja Saxena; Parul Mittal; Nitin Thukral; Eshan Sharma; Anoop Singh; Richa Virmani; Mohita Gaur; et al. (Environmental Microbiology, 2018)
Summary Tuberculosis (TB) is primarily associated with decline in immune health status. As gut microbiome (GM) is implicated in the regulation of host immunity and metabolism, here we investigate GM alteration in TB patients by 16S rRNA gene and whole‐genome shotgun sequencing. The study group constituted of patients with pulmonary TB and their healthy household contacts as controls (HCs). Significant alteration of microbial taxonomic and functional capacity was observed in patients with active TB as compared to the HCs. We observed that Prevotella and Bifidobacterium abundance were associated with HCs, whereas butyrate and propionate‐producing bacteria like Faecalibacterium , Roseburia , Eubacterium and Phascolarctobacterium were significantly enriched in TB patients. Functional analysis showed reduced biosynthesis of vitamins and amino acids in favour of enriched metabolism of butyrate and propionate in TB subjects. The TB subjects were also investigated during the course of treatment, to analyse the variation of GM. Although perturbation in microbial composition was still evident after a month's administration of anti‐TB drugs, significant changes were observed in metagenome gene pool that pointed towards recovery in functional capacity. Therefore, the findings from this pilot study suggest that microbial dysbiosis may contribute to pathophysiology of TB by enhancing the anti‐inflammatory milieu in the host.

Molecular Modeling of Cloned Bacillus subtilis Keratinase and Its Insinuation in Psoriasis Treatment Using Docking Studies - Sonali Gupta; Parul Tewatia; Jyoti Misri; Rajni Singh (Indian Journal of Microbiology, 2017)

Comprehensive assessment of the genes involved in withanolide biosynthesis from Withania somnifera: chemotype-specific and elicitor-responsive expression - Aditya Vikram Agarwal; Parul Gupta; Deeksha Singh; Yogeshwar Vikram Dhar; Deepak Chandra; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2017)

Comparative analysis of transcription factor gene families from Papaver somniferum: identification of regulatory factors involved in benzylisoquinoline alkaloid biosynthesis - Parul Agarwal; Sumya Pathak; Deepika Lakhwani; Parul Gupta; Mehar Hasan Asif; Prabodh Kumar Trivedi (Protoplasma, 2016)

Natural mutations in two homoeologous TT8 genes control yellow seed coat trait in allotetraploid Brassica juncea (AABB) - Lakshmi K. Padmaja; Parul Agarwal; Vibha Gupta; Arundhati Mukhopadhyay; Yaspal S. Sodhi; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2014)

Cloning and functional characterization of 3-hydroxy-3-methylglutaryl coenzyme A reductase gene from Withania somnifera: an important medicinal plant - Nehal Akhtar; Parul Gupta; Neelam Singh Sangwan; Rajender Singh Sangwan; Prabodh Kumar Trivedi (Protoplasma, 2013)

Cloning and characterization of 2-C-methyl-d-erythritol-4-phosphate pathway genes for isoprenoid biosynthesis from Indian ginseng, Withania somnifera - Parul Gupta; Aditya Vikram Agarwal; Nehal Akhtar; Rajender Singh Sangwan; Surya Pratap Singh; Prabodh Kumar Trivedi (Protoplasma, 2013)

Erratum to: Sterol glycosyltransferases-identification of members of gene family and their role in stress in Withania somnifera - Pankaj Chaturvedi; Manoj Mishra; Nehal Akhtar; Parul Gupta; Pratibha Misra; Rakesh Tuli (Molecular Biology Reports, 2012)

Sterol glycosyltransferases-identification of members of gene family and their role in stress in Withania somnifera - Pankaj Chaturvedi; Manoj Mishra; Nehal Akhtar; Parul Gupta; Pratibha Mishra; Rakesh Tuli (Molecular Biology Reports, 2012)

Regeneration of Red Cell Cholinesterase Activity Following Pralidoxime (2-PAM) Infusion in First 24 h in Organophosphate Poisoned Patients - Parul Goel; Nidhi Gupta; Surjit Singh; Ashish Bhalla; Navneet Sharma; K. D. Gill (Indian Journal of Clinical Biochemistry, 2012)

Genetic diversity and relationships among germplasm of Jatropha curcas L. revealed by RAPDs - R. V. Kumar; Yogendra K. Tripathi; Parul Shukla; S. P. Ahlawat; V. K. Gupta (Trees, 2009)

Single-nucleotide variations associated with Mycobacterium tuberculosis KwaZulu-Natal strains - Sarbashis Das; Ragothaman M. Yennamalli; Anchal Vishnoi; Parul Gupta; Alok Bhattacharya (Journal of Biosciences, 2009)

Sequence analysis of the long arm of rice chromosome 11 for rice?wheat synteny - Saurabh Raghuvanshi; Subodh K. Srivastava; Anupama Gaur; Ajit K. Pal; Vivek Dalal; Archana Singh; Irfan A. Ghazi; Ashutosh Bhargav; Mahavir Yadav; Anupam Dixit; Kamlesh Batra; Kishor Gaikwad; et al. (Functional & Integrative Genomics, 2004)

Structural and functional analysis of rice genome - Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Saurabh Raghuvanshi; Anupama Gaur; Anita Kapur; Vikrant Gupta; Dibyendu Kumar; V. Ravi; Shubha Vij; Parul Khurana; Sulabha Sharma (Journal of Genetics, 2004)

Purification and characterization of trypsin inhibitor from seeds of faba bean (Vicia faba L.) - Parul Gupta; Kamal Dhawan; Sarla P Malhotra; Randhir Singh (Acta Physiologiae Plantarum, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)